THE USE OF ORGANIC COMPOUNDS AS MEDICINAL SUBSTANCES - Hikmatova Hilola Ilkhom kizi; Nurmamatova Rukhshona Mardi kizi; Khudoyberdiyeva Farzona Ilkhom kizi; Rayimova Zarina Alisher kizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation: Organic compounds play a fundamental role in modern medicine due  to  their  structural  diversity  and  ability  to  interact  specifically  with  biological targets. This article explores the significance of organic molecules in drug design and development, highlighting their chemical properties, mechanisms of action, and recent advances in pharmaceutical applications. Emphasis is placed on the synthesis of novel compounds, their pharmacodynamics, and the integration of organic chemistry with biotechnology for improved therapeutic outcomes.